Effects of low doping on the improvement of cathode materials Na3+xV2−xMx(PO4)3 (M = Co2+, Cu2+; x = 0.01–0.05) for SIBs. Issue 32 (5th August 2021) - Chen, Ruoyu; Butenko, Denys S.; Li, Shilin; Li, Dongdong; Zhang, Xinyu; Cao, Junming; Ogorodnyk, Ivan V.; Klyui, Nickolai I.; Han, Wei; Zatovsky, Igor V.
Abstract : In this work, we demonstrate the advantages of low doping in relation to the electrochemical properties of the NVP cathode for use in SIBs. Abstract : Doping with metal ions can improve the electrochemical performance of Na3 V2 (PO4 )3 (NVP) as a cathode material for SIBs. Herein, Na3+ x V2− x MII x (PO4 )3 /C composites with low Co- and Cu-doping contents ( x – 0, 0.01, 0.03, 0.05) have been fabricated by a facile sol–gel method. XRD, ICP-AES and XPS studies show that doping with Co 2+ and Cu 2+ does not alter the NVP structure of the material, and cobalt or copper successfully substitute the vanadium in its site. Raman and HRTEM data show the presence of an amorphous carbon coating on the phosphate surface, which increases the electronic conductivity of composites. Impedance spectroscopy suggests that low-level doping has significantly increased the electrical conductivity of the NVP matrix. Among all the samples of the compound, Na3.01 V1.99 Co0.01 (PO4 )3 /C (capacity of 116 mA h g −1 at 0.5C) and Na3.03 V1.97 Cu0.03 (PO4 )3 /C (capacity of 114 mA h g −1 at 0.5C) demonstrate the highest electrochemical ability. Moreover, even cycling at a high rate of 10C, an excellent reversible capacity is maintained at about 80% of the initial values (in the range of 72–89 mA h g −1 ) after 1000 cycles. The presented work analyzes the advantages of low doping and the nature of the doping metal in relation to the electrochemical properties of the NASICON-type structure, which will facilitate further commercialization of SIBs.